Stigma and discrimination against breast cancer survivors in Indonesia: an interpretive phenomenology study - Tisnasari, Ida Ayu Made Ari Santi; Nuraini, Tuti; Afiyanti, Yati (Universitas Airlangga, 2022)
Introduction: Breast cancer is the most common malignancy in women worldwide. Breast cancer and its treatment have a direct impact on all aspects of a woman's life, as well as on breast cancer survivors, thereby affecting the fulfillment of her needs. The purpose of the study is to explore stigma and discrimination against breast cancer sufferers. Methods: This study uses a qualitative method of interpretive phenomenology. Semi-structured interviews were purposively conducted from March to June 2022 with 14 women breast cancer survivors. Results: The three themes identified in this study include: a short duration of survival, being labeled as a suffering person, and social discrimination. Conclusions: Breast cancer survivors experienced stigma regarding their cancer diagnosis. Thus, highlighting the rising need of health professionals' intervention in resolving and adapting to stigma and discrimination regarding breast cancer diagnosis in Indonesia.